2017
DOI: 10.1136/bmjopen-2017-019155
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of appetite loss in addition to existing prediction models for community-acquired pneumonia in the elderly: a prospective diagnostic study in acute care hospitals in Japan

Abstract: ObjectiveDiagnosis of community-acquired pneumonia (CAP) in the elderly is often delayed because of atypical presentation and non-specific symptoms, such as appetite loss, falls and disturbance in consciousness. The aim of this study was to investigate the external validity of existing prediction models and the added value of the non-specific symptoms for the diagnosis of CAP in elderly patients.DesignProspective cohort study.SettingGeneral medicine departments of three teaching hospitals in Japan.Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Furthermore, our findings were not in line with our previous study which suggested the usefulness of self-rated food consumption (using the same definition as the present study) for the diagnosis of community-acquired pneumonia in older patients who presented with upper respiratory symptoms. 11 In this previous study, food consumption with the cut-off of 50% showed Sn of 66.7%, Sp of 79.3%, LR+ of 3.2, LR– of 0.4 and DOR of 7.7 for the diagnosis of community-acquired pneumonia. 11 The previous study aimed to differentiate pneumonia from other viral infection (ie, upper respiratory infection), while we aimed to differentiate bacteraemia from other bacterial infection in the present study.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, our findings were not in line with our previous study which suggested the usefulness of self-rated food consumption (using the same definition as the present study) for the diagnosis of community-acquired pneumonia in older patients who presented with upper respiratory symptoms. 11 In this previous study, food consumption with the cut-off of 50% showed Sn of 66.7%, Sp of 79.3%, LR+ of 3.2, LR– of 0.4 and DOR of 7.7 for the diagnosis of community-acquired pneumonia. 11 The previous study aimed to differentiate pneumonia from other viral infection (ie, upper respiratory infection), while we aimed to differentiate bacteraemia from other bacterial infection in the present study.…”
Section: Discussionmentioning
confidence: 76%
“… 11 In this previous study, food consumption with the cut-off of 50% showed Sn of 66.7%, Sp of 79.3%, LR+ of 3.2, LR– of 0.4 and DOR of 7.7 for the diagnosis of community-acquired pneumonia. 11 The previous study aimed to differentiate pneumonia from other viral infection (ie, upper respiratory infection), while we aimed to differentiate bacteraemia from other bacterial infection in the present study. Thus, the severity between the two conditions was less prominent in the present study than in the previous one, which might have led to the poorer performance of food consumption.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…They also discussed some subtle but important issues that arise when individuals in a population have different costs or benefits from a medical intervention recommended on the basis of predicted risk. Takada et al 10 investigated the external validity of existing prediction models and the added value of the nonspecific symptoms for the diagnosis of community‐acquired pneumonia in elderly patients by using net benefit analysis. Moran and Santamaria 11 investigated the importance of lactate as a risk biomarker in sepsis and septic shock by using decision curve.…”
Section: Introductionmentioning
confidence: 99%